FLIPPED CLASSROOM LEARNING INNOVATION AND CRITICAL THINKING ABILITY OF STUDENTS ON ARGUMENTATION WRITING SKILLS - Heny Kusuma Widyaningrum (RETORIKA: Jurnal Bahasa, Sastra, dan Pengajarannya, 2020)
The purpose of this study is to explain and determine the effect of the Classroom flipped model and the ability of students to think critically. This research is a type of quantitative research using an ex post facto approach with a descriptive correlation design. The research population is fifth-grade students with a total of 25 students. Sampling is done by the saturated sample technique, which uses all members of the population as a sample. Data collection uses the questionnaire and documentation method. In analyzing the data using statistical methods with the product-moment correlation formula and two predictor regression. The results of the study provide information 1) There is an influence of the flipped classroom learning model on the ability to write arguments (r count = 0.745> r table = 0.396). 2) There is an influence of critical thinking ability on the ability to write arguments (r count = 0.608> r table = 0.396). 3) There is a simultaneous influence between the Classroom flipped learning the model and the ability to think critically and the ability to write arguments (Freg = 26.4> Ftable = 3.44).